2021
DOI: 10.9734/ajarr/2021/v15i430387
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chemical Composition of Bryophyllum pinnatum Leaf Ethyl Acetate Fraction

Abstract: Aims: To characterize the chemical composition of Bryophyllum pinnatum leaf ethyl acetate fraction. Methodology: Quantitative phytochemical composition was assessed using gas chromatography fitted with flame ionization detector (GC-FID), while chemical characterization was via gas chromatography-mass spectrophotometry (GC-MS) analysis. The mass spectra peaks were matched with those found in the National Institute of Standard and Technology (NIST) spectral database. Results: Results revealed a rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…They have been used as common agents for the treatment, management and prevention of many diseases in traditional setting, especially in Africa (Nwiloh et al,2016). About 80% of the rural population in the developing world relies on traditional medicines for their health care (Igwe et al,2021). This potential of plants have been ascribed to their rich content of a wide variety of secondary metabolites, such as tannins, saponins, alkaloids, flavonoids, etc (Nwiloh et al,2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been used as common agents for the treatment, management and prevention of many diseases in traditional setting, especially in Africa (Nwiloh et al,2016). About 80% of the rural population in the developing world relies on traditional medicines for their health care (Igwe et al,2021). This potential of plants have been ascribed to their rich content of a wide variety of secondary metabolites, such as tannins, saponins, alkaloids, flavonoids, etc (Nwiloh et al,2016).…”
Section: Introductionmentioning
confidence: 99%
“…GC-FID analysis revealed the presence of dihydrocytisine, ammodendrine, spartein, hydroxylupanine, ribalinidine, anthocyanin, flavone, flavonones, aphylidine, proanthocyanidin, isolupanine, narigenin, sapogenin, cardiac glycoside, tannin, and cyanogenic glycoside in varying proportions. GC-MS analysis identified 14 constituents with major ones being 2,6-Octadienal, 3,7-dimethyl-, (Z) Citral (14.88 %), citral 2,6-Octadienal, 3,7dimethyl-, (E) (16.9 %), cis-3-Hexenyl cis-3hexenoate (10.59 %), trans-2,7- 8,4).0(7,9)] undecane (11.69 %). This study has shown that crude phenolic leaf extract of A. wilkesiana contains pharmacologically active compounds which support its traditional use in the treatment of oxidative stress related diseases and hence a potential candidate for drug discovery.…”
mentioning
confidence: 99%
“…18,19 The chemical composition, hepatoprotective activity, anti-ulcer activity, in vitro and in vivo anti-inflammatory and free radical scavenging activities of the leaf, root has also been reported. 20,21,22,23…”
Section: Introductionmentioning
confidence: 99%
“…"Chemical composition, hepatoprotective activity, antiinflammatory effects, anti-ulcer activity, and free radical scavenging activities have also been reported" [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%